Diversification of IFNγ-inducible CXCb chemokines in cyprinid fish - van der Aa, Lieke M.; Chadzinska, Magdalena; Derks, Wouter; Scheer, Marleen; Levraud, Jean-Pierre; Boudinot, Pierre; Lidy Verburg-van Kemenade, B.M. (Developmental and comparative immunology, 2012)
We earlier identified two CXCL8-like lineages in cyprinid fish, which are functional homologues of the mammalian CXCL8, but with diverged functions. We here investigated whether the carp IFN-γ-inducible CXCb gene, related to the mammalian CXCL9, -10 and -11 chemokines, was subject to a similar diversification. On the zebrafish genome, a cluster of seven CXCb genes was found on chromosome five. Analysis of the promoter of the zebrafish CXCb genes suggests a partially shared, but differential induction. A second CXCb gene, CXCb2, was identified in common carp by homology cloning. CXCb2 is constitutively expressed in immune-related tissues, predominantly in head kidney lymphocytes/monocytes. Interestingly, an induction of CXCb2 gene expression with recombinant carp IFN-γ2 and LPS was observed in macrophages and granulocytes. Finally, difference in sensitivity to LPS, and kinetics of CXCb1 and CXCb2 gene expression during zymosan-induced peritonitis, was observed. These results indicate a functional diversification for cyprinid CXCb chemokines, with functional homology to mammalian CXCL9–11.